2023
DOI: 10.1093/rheumatology/kead445
|View full text |Cite
|
Sign up to set email alerts
|

Significant nailfold capillary loss and late capillaroscopic pattern are associated with pulmonary arterial hypertension in systemic sclerosis

Rossella De Angelis,
Valeria Riccieri,
Edoardo Cipolletta
et al.

Abstract: Objectives To evaluate differences in nailfold videocapillaroscopy (NVC) findings between systemic sclerosis-SSc patients with and without a diagnosis of pulmonary arterial hypertension (PAH). Methods 110 SSc patients were enrolled in this cross-sectional, case-control, multi-centre study. Patients were divided into cases (SSc-PAH confirmed by right hearth catheterization-RHC) and controls (SSc-nonPAH with low probability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We found that a reduced DLco of 72.3% exhibits the best probability to be associated with SSc-ILD. Of note, DLco could be reduced if concomitant PAH and/or emphysema are present, but it should be mentioned that in our study, patients with a high probability of PAH according to the DETECT algorithm and/or PAH diagnosed by RHC and/or with chronic lung disease other than SSc-ILD were excluded [11,16,28,31,34]. Questionnaires assessing dyspnoea in SSc-ILD as well as quality of life are used in clinical practice [10,20,35], especially for correlation with the extent of pulmonary involvement [10,20].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We found that a reduced DLco of 72.3% exhibits the best probability to be associated with SSc-ILD. Of note, DLco could be reduced if concomitant PAH and/or emphysema are present, but it should be mentioned that in our study, patients with a high probability of PAH according to the DETECT algorithm and/or PAH diagnosed by RHC and/or with chronic lung disease other than SSc-ILD were excluded [11,16,28,31,34]. Questionnaires assessing dyspnoea in SSc-ILD as well as quality of life are used in clinical practice [10,20,35], especially for correlation with the extent of pulmonary involvement [10,20].…”
Section: Discussionmentioning
confidence: 85%
“…Our results suggest that all patients diagnosed with SSc should receive a comprehensive clinical assessment, including PFTs, assessment of respiratory symptoms and oesophageal involvement, and NVC, to ensure early identification of ILD, especially in those without clear evidence of interstitial disease at HRCT, or without the classic risk factors, or even in situations where a CT scan cannot be performed quickly, providing baseline measurements to compare with upcoming assessments [3,6,7,9]. Alongside more widespread measures in clinical practice, namely DLco and/or patient-reported questionnaires, there are increasing reports indicating that NVC, a safe and validated tool, particularly the highly reliable measurement of capillary density [48], may be incorporated in high-performance algorithms for the early detection of lung involvement in SSc [9,13,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a reduced DLco of 72.3% exhibits the best probability of being associated with SSc-ILD. Of note, DLco could be reduced if concomitant PAH and/or emphysema are present, but it should be mentioned that in our study, patients with a high probability of PAH according to the DETECT algorithm and/or PAH diagnosed by RHC and/or with chronic lung disease other than SSc-ILD were excluded [ 11 , 16 , 28 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-haemorrhages and micro-thrombosis were excluded from the counting process. A consensus concerning image acquisition and analysis, scoring system and reliability of image acquisition and interpretation had already been reached by the authors (RDA, EC, FF) [ 26 , 28 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%